Intravenous phytonadione administered orally in reducing warfarin-related coagulopathy. (3rd April 2022) - Rice, Jordan H.; Akpunonu, Peter; Davis, George A.; Dugan, Adam; Litteral, Jamie; Webb, Ashley N.; Wiegand, Alexandra; Bailey, Abby; Baum, Regan A.
Abstract: Introduction: The cost of phytonadione tablets has increased markedly and is significantly higher than the intravenous formulation. The intravenous formulation given orally is a potential alternative but has not been directly evaluated in comparison to the commercially available tablet. The objective of this study was to evaluate the efficacy of phytonadione intravenous solution given orally compared to commercially available phytonadione tablets for reversal of coagulopathy related to warfarin. Methods: We conducted a retrospective, observational study of adult patients who received phytonadione tablets and the IV formulation orally for warfarin-related coagulopathy. The international normalized ratio (INR) was measured before and after phytonadione administration. The primary outcome was INR <1.5 at 24 h after phytonadione administration. Results: From January 1, 2015 to August 1, 2018 a total of 200 patients were identified. In total, 58% ( n = 116) patients received IV phytonadione solution given orally and 42% ( n = 84) patients received the tablets. The primary outcome of INR <1.5 at 24 h was not significantly different between groups ( p = 0.321). Discussion: The IV phytonadione solution given by mouth and the tablet formulation performed similarly.